Letter : Spanish seamen - Hallsworth, Joseph
025a-0033-001 Rec AC. 15.X.40 Telephone RUSHOLME 2504 5 Registered Trade Union No. 1798T Telegrams RUSHOLME 2804 National Union of Distributive and Allied Workers J. Hallsworth W.A.Robinson General Secretaries Registered Office Oakley 122, Wilmstow Road, Manchester, 14. In replying please quote 5725.RAC/RC 15th July 1940 The General Secretary, Trades Union Congress, Transport House, Smith Square, S.W.1. Dear Colleague, Spanish Seamen Your letter of the 5th instant (reference WMC/HVT/FC/620) requesting a further donation in order to maintain the payment of allowances to Spanish seamen still in this country who declined to sale their boats back to Spain, was brought to the notice of my Executive Council at their meeting held this last weekend. They very readily decided to meet the call for a further donation of £40., and I have pleasure in enclosing cheque herewith. I shall be glad to have your receipt in due course, worded as follows so as to keep the payment in conformity with the rules of this Union - "As a contribution in aid of the Spanish Trade Union Movement." Yours sincerely, , J. Hallsworth Industrial General Secretary. Enclosure 292/946/25a/33